Gut microbiota associated with pulmonary tuberculosis and dysbiosis caused by anti-tuberculosis drugs. Issue 4 (April 2019) - Hu, Yongfeng; Yang, Qianting; Liu, Bo; Dong, Jie; Sun, Lilian; Zhu, Yafang; Su, Haoxiang; Yang, Jian; Yang, Fan; Chen, Xinchun; Jin, Qi
Summary: Background: An improved understanding of the gut microbiota could lead to better strategies for the diagnosis, therapy and prophylaxis of tuberculosis (TB). The impact of both Mycobacterium tuberculosis (Mtb) infection and anti-TB treatment on the gut microbiota has rarely been studied. Methods: We characterized the diversity and composition of the gut microbiota in pulmonary TB patients as well as the effects of anti-TB drugs on the gut microbiota. Results: Pulmonary Mtb infection led to a minor decrease in the α diversity of the gut microbiota when compared to healthy controls, which mainly resulted from changes in the relative abundance of the members of genus Bacteroides . Anti-TB therapy caused a rapid, significant alteration in the community structure. The relative abundance of members of genus Clostridiales of the phylum Firmicutes significantly decreased during anti-TB treatment, while many members of genus Bacteroides, including Bacteroides OTU230 and Bacteroides fragilis, were among the taxa that increased. OTU8 and OTU2972 assigned to family Erysipelotrichaceae of the phylum Firmicutes showed a dramatic increase 1 week after the start of therapy, while the other members of this family decreased. Conclusions: Pulmonary TB and anti-TB treatment caused a distinct dysbiosis of the gut microbiota. Our study contributes valuable information implying potential links between the gut microbiota and TB.